USE OF SOLID-STATE NANOPORES FOR THE CHARACTERIZATION AND QUANTIFICATION OF HYALURONIC ACID (HA) AS A DISEASE BIOMARKER IN BIOLOGICAL FLUIDS AND TISSUES - Rivas Duarte, Felipe (Wake Forest University, 2022)
Hyaluronan (or hyaluronic acid, HA) is linear glycosaminoglycan (GAG) at physiological pH, that is composed of the alternating disaccharide repeat structures [-4-D-glucuronic acid-β1-3-N-acetylglucosamine-β1-] n. Structurally, HA does not exhibit the substituent sulfation that is typical of other GAGs, resulting in a consistent chemical configuration and negative electrostatic charge at physiological pH. It is a ubiquitous molecule that plays critical roles in numerous physiological functions in vivo, including tissue hydration, extracellular matrix structure, innate immunity and joint protection and lubrication. Physiologically HA is found over a wide range of molecular weights (MW) due to the broad metabolic and catabolic pathways it is associated with, strongly liking a size-function relationship in the many diverse functions it performs. Typically, HA’s MW spans a range from a few oligosaccharides (1 disaccharide is 400 Da and corresponds to ~1 nm) to up to at least 25,000 disaccharide units (10 MDa, 25 μm), which is typically further classified as high MW-HA (HMW-HA, ~>500kDa) and low MW-HA (LMW-HA, <~200kDa), or in some cases over a narrower distinction of MW range depending on the cell or tissue type it interacts with. It is typically associated that an increased presence of LMW-HA plays a pro-inflammatory role while HMW-HA is associated with anti-inflammatory effects. This size-dependent behavior has been reported in process such as joint lubrication, angiogenesis, tumorigenesis and cell migration and differentiation. For this reason, both the abundance and MW of site-specific HA are considered important bioindicators of disease pathophysiology and inflammation, making it a valuable potential diagnostic biomarker. However, current methods to either quantify (e.g., ELISA) or determine size of HA (e.g., mass spectrometry, gel electrophoresis, size exclusion chromatography) are separate and can suffer challenges in terms of dynamic range, quantitative output, and/or sample mass requirements. Many key technologies also require specialized equipment and expertise, limiting their accessibility. Thus, there is a need for improved HA analytical and detection methods. In response to these limitations, this research proposal focuses on adapting the use of solid-state nanopores (SS-NPs) for the molecular size and concentration determination of HA, as this analytical technique has shown to be successfully employed in studying small organic protein molecules, and in detecting nucleic acid and polymeric DNA and RNA strands, on a single molecule basis, whilst providing information on length and concentration, from small sample size volumes. SS-NPs are an emerging analytical platform consisting of a single nanometer-scale aperture through which charged biomolecules can be threaded electrically and interrogated individually by examining the resulting transient interruptions in the ionic current blockage (i.e., translocation ‘events’) to yield data at the single-molecule level. The duration and amplitude of translocation events are determined primarily by molecular size, whereas the frequency in which the ‘events’ occur can provide information regarding the concentration of the analyte of interest. Therefore, it is the overarching aim of this research project is to establish the SS-NPs as an analytical tool that can provide reliable, quantitative determination of HA abundance and MW distribution in the same platform and simplify the technical demands associated with HA assessment in biological samples, such that it become a tool of potential translational diagnostic applications and/or for basic science research. This dissertation is divided into five chapters. CHAPTER 1 will review the biophysical properties of HA, its biological role, and its importance as a biomarker in different disease conditions. It will also introduce the applications and governing principles of nanopore technology for single molecule detection measurements. CHAPTER 2 will cover experimental validation of the use of SS-NPs as an analytical tool for the measurement of HA concentration and MW determination and expand on its use in detecting of other glycans. CHAPTER 3 will discuss how changes in the experimental conditions including measurement buffer (using both symmetric and asymmetric conditions), SS-NP size, and voltage can improve the sensitivity and resolution of the signal for optimal detection of HA. CHAPTER 4 will then discuss the general isolation and extraction protocol of HA that has been successfully adapted for biological fluids (e.g., blood, synovial fluid, urine, lung lavage) and tissue specimens specifically tailored for downstream analysis with SS-NPs. The versatility of this protocol and high purity yield extraction combined with the use of SS-NPs will be demonstrated evaluating biological fluids and tissue specimen of animal models of osteoarthritis (OA), and tissue aging effects in ovarian tissue. Finally in recognizing potential limitations of the isolation and extraction protocol, CHAPTER 5 will introduce a proof-of-concept magnetophoretic microfluidic device (MMFD) design to overcome extraction bias and improve MW distribution capture fidelity. This final chapter will show how controlled fluid properties achieved by microfluidics can enhance substrate-HA mixing and improve MW distribution capture fidelity by reducing the effects of MW bias in the extraction of HA. The low-cost design, ease of assembly and more importantly potential for scalable automated extraction will also help to reduce extraction time and yield, bringing this technology one step closer for use in translational applications. It is the overarching intent of this dissertation to present a novel adaptation of SS-NP technology to the measurement of HA bridging a gap in the current state of the art technology and serve as the basis to expand to future glycan molecular biomarker detection of clinical importance.
Keywords: Biomarkers; Biopolymers; Glycosaminoglycans; Hyaluronic Acid; Nanotechnology; Solid-State Nanopores